FEMINISM BASED ON THE HEGEMONY OF GENDER FOUND IN THE AUTOBIOGRAPHY OF GADIS ARIVIA - Hidayatul Munawaroh; Sulistyaningsih Sulistyaningsih (STKIP PGRI SIDOARJO, 2023)
Abstract Women have the right to obtain higher education and other rights as men. This study about